2011
DOI: 10.1002/ccd.23406
|View full text |Cite
|
Sign up to set email alerts
|

The fellows stitch: Large caliber venous hemostasis in pediatric practice

Abstract: A subcutaneous figure of eight suture hemostasis strategy can provide a safe and efficient method for large caliber venous hemostasis in a pediatric practice with improved hemostasis times and no additional morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…This may require an extended period of pressure, which is stressful to children. According to previous literature, the average time of manual compression is 14 minutes (8–30 minutes) . In our center, the time of manual compression was 10–14 minutes.…”
Section: Introductionmentioning
confidence: 67%
“…This may require an extended period of pressure, which is stressful to children. According to previous literature, the average time of manual compression is 14 minutes (8–30 minutes) . In our center, the time of manual compression was 10–14 minutes.…”
Section: Introductionmentioning
confidence: 67%
“…Morgan et al and Zhou et al published a case series demonstrating feasibility and safety of the “Z”‐stitch in children after structural interventions using 6–22 F sheath . More recently, three other nonrandomized studies confirmed safety and efficacy of the method in patients undergoing catheter ablation of atrial fibrillation with the use of 15 F sheaths .…”
Section: Discussionmentioning
confidence: 99%
“…Both passages were done deeply under the skin to grasp as much of the underlying subcutaneous, adipose tissue as possible. Deep stitching was facilitated by modification of the original technique of subcutaneous “Z” or “figure‐of‐eight” suture where it was advised to pass the suture perpendicularly to the sheath . The modified technique introduced at our center (MD) uses longitudinal passage of the suture, which allows for deeper stitching while mitigating the risk of vessel injury.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using venography and vascular ultrasound imaging modalities had demonstrated the safety and efficacy of the F-8 suture technique for femoral venous hemostasis [10][11][12][13][14][15]. This technique produces compression the femoral vein at the sheath entry point by the external soft tissue to achieve hemostasis, without causing thrombus, embolism, or venous stenosis.…”
Section: Prior Studies Of the F-8 Suture Techniquementioning
confidence: 99%